Complete Nucleotide Sequence of pK245, a 98-Kilobase Plasmid Conferring Quinolone Resistance and Extended-Spectrum-β-Lactamase Activity in a Clinical Klebsiella pneumoniae Isolate - Chen, Ying-Tsong (American Society for Microbiology, 2006)
A plasmid containing the qnrS quinolone resistance determinant and the gene encoding the SHV-2 β-lactamase has been discovered from a clinical Klebsiella pneumoniae strain isolated in Taiwan. The complete 98-kb sequence of this plasmid, designated pK245, was determined by using a whole-genome shotgun approach. Transfer of pK245 conferred low-level resistance to fluoroquinolones in electroporant Escherichia coli epi300. The sequence of the immediate region surrounding qnrS in pK245 is nearly identical (>99% identity) to those of pAH0376 from Shigella flexneri and pINF5 from Salmonella enterica serovar Infantis, the two other qnrS-carrying plasmids reported to date, indicating a potential common origin. Other genes conferring resistance to aminoglycosides (aacC2, strA, and strB), chloramphenicol (catA2), sulfonamides (sul2), tetracycline (tetD), and trimethoprim (dfrA14) were also detected in pK245. The dfrA14 gene is carried on a class I integron. Several features of this plasmid, including three separate regions containing putative replicons, a partitioning-control system, and a type II restriction modification system, suggest that it may be able to replicate and adapt in a variety of hosts. Although no critical conjugative genes were detected, multiple insertion sequence elements were found scattered throughout pK245, and these may facilitate the dissemination of the antimicrobial resistance determinants. We conclude that pK245 is a chimera which acquired its multiple antimicrobial resistance determinants horizontally from different sources. The identification of pK245 plasmid expands the repertoire of the coexistence of quinolone and extended-spectrum-β-lactam resistance determinants in plasmids carried by various species of the family Enterobacteriaceae in different countries.